Evaluating Factors of Language Proficiency and Cultural Shock and Adjustment through Analyzing Contents of “English Vinglish” Movies: A TESOL and Sociological Perspective - Lina Aris Ficayuma (STKIP AL HIKMAH SURABAYA, 2024)
This study aims to evaluate language proficiency factors, cultural shock and adjustments who influence the language learners at multicultural classroom through content analysis at English Vinglish movies based on the principle of TESOL, sociological and cross culture understanding perspective. To obtain the data, this study uses descriptive methods and applied content analysis techniques to know an overview of the message delivered systematically. The researcher uses six (pre-service teachers) rather to validate the result of content analysis. The research finding show that: 1) There are 5 factors who determine the language proficiency of multi-ethnic language learners in ESP class; a) obtaining supportive environment and living at inner circle country , b) having extrinsic motivations, c) desiring to growth occupation and social status in positive way, d) designing an interactive communication activities and creative teaching strategies, e) Influenced by sociological perspective such as normative, psychological, and socio-structural. Meanwhile, there are 4 stage of culture shock and adjustment was faced the main actors; honeymoon phase, 4 crisis phrases, recovery phrase, and adjustment phrase. The ethnic identity who learner come from is various countries; India, Mexico, French, China, Africa, and France.